Students' Scientific Literacy Skills by Using Big book-based Science Textbooks (Changes in Form of Objects) - Rora Rizky Wandini; Sholihatul Hamidah Daulay; Emeliya Sukma Dara Damanik; Mardianto Mardianto; Akhyaruddin Akhyaruddin (LPPM Universitas Pahlawan Tuanku Tambusai, 2022)
Big books are learning media that can be used as learning resources by presenting of contextual and interactive images in increasing of students' literacy skills. Good literacy skills will make easy for students to understand the meaning of the information provided and they can improve their interpersonal skills well. This research is a quantitative research with a survey approach. Participants in this study are 237 students. Data collection was obtained from interviews and questionnaires, then analyzed using the percentage technique. The results of this study illustrate that using big book-based science textbooks, students' scientific literacy skills can increase. The results shows that literacy in context, knowledge, competence, and attitude are categorized good.